Persepsi Tubuh dan Implikasinya Terhadap Kepercayaan Diri Remaja - Nabila Dwi Putri; Indah Permata Sari; Risma Anita Puriani (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Adolescence is a critical stage of development marked by various significant changes, both physically and cognitively. These changes influence adolescents’ self-perception, particularly regarding their body image and appearance. This study aims to explore the implications of body perception on self-confidence in adolescents, utilizing a literature review method. The research is based on an analysis of 20 scientific articles published between 2020 and 2026, all of which address body perception and self-confidence. The findings reveal a generally positive relationship between body perception and self-confidence, as most studies indicate that adolescents with positive body image tend to exhibit higher levels of self-confidence. However, some studies highlight the challenges faced by adolescents with negative body image, often correlating with lower self-confidence levels. This discrepancy suggests that while positive body perception can enhance self-confidence, negative body image may hinder the development of healthy self-esteem. In conclusion, body perception plays a crucial role in shaping adolescents' self-confidence, emphasizing the importance of fostering positive body image during this developmental stage to support psychological well-being.